Environmental Accounting: A Map Of Environmental Regulations And Policies Of The Indonesian Central Government - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2005)
This paper is mapping the environmental regulations and policies of the Indonesian Government. The regulations and policies are analyzed into the area of the environmental accounting. There are four direct regulations relating to environmental concerns: Code Number 23/ 1997 about Environment Management, Code Number 19/2004 about Forestry, Government Decree Number 74/ 2001 about dangerous and poisonous material management, and Environmental Minister Decree Number 113/ 2003 on Water Pollution Quality Standard of the businesses and/ or Coal Mining Activities. The regulations have potentials to support the development of environmental accounting to be implemented in the business activities in Indonesia.